Culicoídes (Diptera: Ceratopogonídae) na Amazônia Brasileira. I. Coletas na Usina Hidrelétrica (UHE) de Balbina, Usina Hidrelétrica (UHE) Cachoeira Porteira e Cachoeira dos Espelhos (Rio Xingú) - Castellón, Eloy Guilhermo (Acta Amazonica, 2020)
Working in tree different areas in the Brazilian Amazon , was catched twenty two species of Culicoides, which four species yet not have been collected in the Amazon Region: C. efferus Fox, C. lahillei Wirth & Blanton, C. spurius Wirth & Blanton an C. verecundus Macfie. Biting midges were distributed for areas and according to hight of collected with CDC light traps; are relationed the names of 63 species at now reported in the brazilian Amazon basin.